Police and civil society partnership: Peculiarities of implementation in modern conditions - Ivanovych Teremetskyi, Vladyslav; Vasylovych Novichenko, Andrii; Borysivna Bodnar-Petrovska, Olha; Petrivna Mkhmurova-Dyshliuk, Olena; Leonidivna Hrihorova, Hanna (Edelweiss Applied Science and Technology, 2024)
The purpose of the article is to find out the peculiarities of the implementation of partnership relations between the police and civil society in modern conditions, based on the analysis of current Ukrainian and foreign legislation, as well as scientific literature. Partnership as a type of social interaction is characterized by the authors of the article. The essence of the term “partnership” in modern foreign science is analyzed. The main features of the partnership model of interaction of subjects are characterized, with an emphasis on the partnership between the police and civil society institutions. The main components of the mechanism of partnership interaction between the institutions of the State and civil society institutions in the field of law enforcement are considered. The experience of different countries related to the partnership of law enforcement agencies and civil society institutions is described, with the aim of promoting the formation of effective forms of partnership between the police and civil society institutions in modern Ukraine. The importance of building in Ukraine an effective partnership model of cooperation between the police and civil society institutions in modern Ukraine is emphasized. The importance of public participation in the implementation of state functions in the field of security in modern conditions is proved. The importance of trust for effective partnership is emphasized.